Identification Risk Factors of Stroke: Literature Review - Agianto Agianto; Bellia Yulise; Rismia Agustina; Ichsan Rizany (Berkala Kedokteran, 2022)
State spending to deal with stroke is quite large every year due to the high incidence of stroke. Data from the Ministry of Health of Indonesia mentions an increasing number in health financing every year, the country financed stroke services by 2.56 trillion in 2018. The magnitude of the incidence of stroke can be lowered by controlling the risk factors of stroke. This study aimed to identify stroke risk factors, both those modifiable risk factors and irreversible risk factors. Research is conducted with a literature review using descriptive study methods or correlation analysis with cross sectional approaches. Sixteen articles identified from Google scholars and Garuda databases in the 2015-2020 range, and were analysed using JBI critical appraisal tools-checklist for analytical cross-sectional studies and JBI critical appraisal tools-checklist for prevalence studies.  Synthesis narrative was used to analyse the articles. Out of 16 articles examined the modifiable risk factors were hypertension, dyslipidemia, diabetes mellitus, lack of physical activity, blood sugar levels, cholesterol levels in blood, alcohol and drug consumption, kidney disease, tuberculosis, heart disease, heart failure, obesity, central obesity, atrial fibrillation and also smoking are declared associated with the incidence of stroke. The irreversible risk factors are age, gender, education, family history, income employment, previous stroke history, and rural and urban distribution. Risk factors divided into two categories modifiable risk factors and irreversible risk factors. It is important to know the risk factors of stroke in order prevent the occurrence of stroke as early as possible by avoiding modifiable stroke risk factors. Hypertension, smoking, diabetes mellitus obesity, dyslipidemia, and lack of activity are the most modifiable stroke risk factors identified in the articles. The most irreversible risk factors identified in the article are age, gender, and level of education